Gastrointestinal parasitic infestation in the Rock ptarmigan Lagopus muta in the French Alps and French Pyrenees based on long-term sampling (1987–2018). Issue 7 (1st June 2020) - Fanelli, Angela; Tizzani, Paolo; Belleau, Eric
Abstract: Data presented in this work represents the first record of parasites from the Alpine and Pyrenean Lagopus muta subspecies, providing valuable information to consider for conservation management. From 1987 to 2018, 207 Rock ptarmigans were collected in the framework of a long-term sanitary monitoring in France. Eight parasites were found in the Alpine Rock ptarmigan, and one in the Pyrenean subspecies. Only two parasites occurred with high prevalence in the Alpine Rock ptarmigan: Capillaria caudinflata (38.9%) and Eimeria sp. (34.7%). Prevalence of the other parasites ( Ascaridia compar, Cestodes, Amphimerus sp. and Trichostrongylus tenuis ) was lower than 20%. Dispharynx nasuta was found with a prevalence of 52.9% in the Pyrenean Rock ptarmigan. Overall, we found a spatially aggregated distribution of parasites in the northern French Alps, probably due to both favourable climatic conditions for parasite cycle and high host density. Statistical analyses indicated a positive effect of altitude and latitude on C. caudinflata occurrence whereas risk factors for Eimeria sp. were the distance from urban areas and land cover. In addition, the majority of the infested birds came from areas close to ski-pistes, where human disturbance increases the susceptibility to diseases, causing stress to wildlife.